The pathology, phylogeny, and epidemiology of Echinococcus ortleppi (G5 genotype): a new case report of echinococcosis in China - Xu Wang (BMC, 2021)
Abstract Background Cystic echinococcosis (CE), caused by the larval stage of the complex Echinococcus granulosus sensu lato (s.l.), is a zoonotic parasitic disease with a high social burden in China. E. ortleppi is a species (formerly genotype 5 of E. granulosus s.l.) with unique epidemic areas (tropical areas), transmission patterns (mainly cattle origin), and pathological characteristics (large and small hook lengths) compared to other species that cause CE. A 19-year-old female patient in an area with no history of echinococcosis in Guizhou Province, China, was diagnosed with E. ortleppi infection in 2019. This study is to understand the source of this human E. ortleppi infection. Methods We performed computer tomography (CT) scans, surgical operation, morphological sectioning, molecular diagnosis, phylogenetic analyses, and epidemiological investigation in Anshun City, Guizhou Province, China in 2019. Results The patient presented with intermittent distension and pain in the upper abdomen without other abnormal symptoms. Routine blood examination results were normal. However, abdominal CT revealed a fertile cyst with a diameter of approximately 8 cm, uniform density, and a clear boundary, but without an evident cyst wall in the right lobe of the liver. The cyst was fertile, and phylogenetic analyses revealed that the isolates represented a new E. ortleppi genus haplotype. A result of 10‒14 years incubation period with indigenous infection was considered available for the case through the epidemiological survey. Conclusions CE due to E. ortleppi infection can be confused with other diseases causing liver cysts, resulting in misdiagnosis. A transmission chain of E. ortleppi may exist or existed in the past in the previously considered non-endemic areas of echinococcosis in southwestern China. Graphic abstract